Neurofinance: Α collaboration of psychology, Neurology and investor behavior - Diacogiannis, George; Bratis, Theodoros (SPOUDAI Journal of Economics and Business, 2010)
This article reviews the recent scientific contributions which led to the emergence of the new multidisciplinary domain research of neurofinance, as a subsector of behavioral finance. Neurofinance as a cross-disciplinary field integrating Neurophysiology, Psychology and Finance adds to the classic financial theory the principles of neuroscience and psychology, putting as bases new axiomatic proposals, which Financial Science use in the field of decision-making in the status of uncertainty and risk. The benefits of the development of Neurofinance offer an alternative approach to the inside understanding of the selection procedure during investing, turning the focus from Homo Economicus to Homo Irrationalis. JEL Classifications: G00, D82, D87. ___________________________________________________ Νευροχρηματοοικονομική: Μια συνεργασία ψυχολογίας, νευρολογίας και επενδυτικής συμπεριφοράς Το παρόν άρθρο διαπραγματεύεται την επισκόπηση των σύγχρονων επιστημονικών συμβολών που οδήγησαν στην ανάδυση του διεπιστημονικού τομέα έρευνας της Νευροχρηματοοικονομικής (Neurofinance) ως κλάδου της Συμπεριφορικής Χρηματοοικονομικής (Behavioral Finance). Η Νευροχρηματοοικονομική ως διεπιστημονικός τομέας έρευνας της Νευροφυσιολογίας, Ψυχολογίας και Χρηματοοικονομικής, έρχεται να προσθέσει στην κλασική χρηματοοικονομική θεωρία τις αρχές της Νευροεπιστήμης και της Ψυχολογίας, θέτοντας εκ νέου τις βάσεις αξιωματικών προτάσεων στις οποίες στηρίζεται η Χρηματοοικονομική όσον αφορά τον τομέα λήψης αποφάσεων σε καθεστώς αβεβαιότητας και κινδύνου. Τα οφέλη από την ανάπτυξη της Νευροχρηματοοικονομικής, προσφέρουν μια εναλλακτική προσέγγιση στην εκ των έσω κατανόηση της διαδικασίας επιλογής επενδύσεων, εκτρέποντας το ενδιαφέρον από τον Homo Economicus στον Homo Irrationalis.